Education on the integration of probiotic fish pellet production with aquaponic technology as a solution for food self-sufficiency - Praja, Rian Ka; Dwijayanti, Rts. Sherly; Saputra, Rizki Rachmad; Decenly, Decenly; Suma, Joy Angel Aria; Harianja, Henrigen (Community Empowerment, 2025)
This community service program was carried out in Talian Kereng Village, Katingan Regency, Central Kalimantan, with the aim of enhancing food self-sufficiency through training on probiotic-based fish pellet production and the implementation of aquaponic technology. The program involved 15 participants and included theoretical training sessions, practical fish feed production, and aquaponic system installation. Evaluation results indicated a significant increase in knowledge, with the average score rising from 40% to 85%. A total of 90% of participants successfully practiced fish pellet production with the correct composition, while 80% were able to independently operate the aquaponic system. The program also featured the handover of fish pellet production technology and the aquaponic system to the local fish farming group. Despite challenges related to the availability of probiotic ingredients and aquaponic system management, this initiative has opened opportunities for further development in rural fisheries and agriculture.